Optimization of Extraction Process, Structural Characterization and in Vitro Bioactivity of Polysaccharides from Dendrocalamus brandisii Bamboo Shoot Shell - Jingjie LIU; Xiaowei PENG; Anna WANG; Wenxi XIA; Changwei CAO; Huan KAN; Yun LIU (Shipin gongye ke-ji)
The extraction process of polysaccharides from Dendrocalamus brandisii bamboo shoot shell (PDB) was optimized by Box-Behnken response surface method, and high performance gel permeation chromatography, ion chromatography, ultraviolet spectroscopy, and Fourier infrared spectroscopy were comprehensively applied, scanning electron microscopy, and Congo red assay were used to characterize the structure of PDB separated by DEAE-52 cellulose column, and to evaluate the in vitro antioxidant, hypoglycemic, and hypolipidemic activities of each component. The results showed that the highest percentage of available of PDB was 2.09% when the concentration of sodium carbonate was 4.1 mg/mL, the ultrasonic power was 310 W, the ultrasonic time was 81 min, and the ultrasonic temperature was 66 ℃. PDB was separated by a DEAE-52 cellulose column to obtain the three fractions, namely PDB-0, PDB-1, and PDB-2, which were all mainly composed of arabinose, galactose, glucose and xylose, and the IR spectra showed that the three fractions had typical polysaccharide characteristic peaks. In vitro bioactivity experiments revealed that all three polysaccharide fractions exhibited certain antioxidant, hypoglycemic and hypolipidemic activities, among which the antioxidant activity of PDB-2 was the most prominent, with the half-inhibitory concentrations (IC50) of 0.74±0.05 mg/mL and 0.64±0.01 mg/mL, respectively, for the removal of DPPH· and ABTS+·. When the concentration was 1 mg/mL, the absorbance value of the iron reduction assay was 0.331; the IC50 values for the inhibition of α-amylase activity by each component were 0.78±0.05, 0.82±0.04 and 0.94±0.02 mg/mL, respectively, at concentrations of 1 mg/mL, the binding ratios of PDB-0, PDB-1 and PDB-2 to sodium cholate, sodium taurocholate, and sodium glycylcholate were respectively up to 17.66%±0.12%, 21.06%±0.45%, and 22.28%±0.51%; 24.79%±0.79%, 26.27%±0.78%, and 32.57%±0.75%; 22.46%±0.79%, 25.52%±0.23% and 23.16%±0.78%. In summary, PDB has good in vitro antioxidant, hypoglycemic and hypolipidemic activities and has great potential in the development of food antioxidants and nutraceuticals.